Low morphology does not lower success after intrauterine insemination unless inseminating motile sperm count is low - Heather Burks; Jennifer D. Peck; Karl R. Hansen; Julie Stoner; LaTasha B. Craig (PLoS ONE, 2025)
The objective of this study was to determine the relationship between strict morphology as assessed on the initial semen analysis during fertility workup and pregnancy rates after intrauterine insemination. This is a retrospective study of couples undergoing intrauterine insemination from 2007 to 2012. Couple characteristics and semen analysis parameters were recorded and evaluated. Risk ratios (RR) and 95% confidence intervals (95% CI) were calculated, accounting for within-couple (cluster) correlation among repeated intrauterine insemination cycles. Four hundred thirty-five women (average ±  standard deviation age 31.7 ±  4.8) undergoing 1,287 intrauterine insemination cycles were analyzed. Fecundability was not statistically different when low strict morphology (≤1% and 2-4%) was compared to the reference range of morphology > 14% [RR 0.99 (0.41-2.40) and 0.90 (0.48-1.70)]. Results were unchanged when adjusted for female characteristics, medication, and inseminating total motile sperm count [aRR 1.22 (0.51-2.93) and 1.00 (0.53-1.91)]. Evaluating combined effects of morphology with inseminating total motile sperm count, pregnancy rates among cycles with total motile count <  5 million and strict morphology ≤  4% normal were reduced when compared to cycles with total motile count > 20 million and morphology > 4% normal (RR 0.37, 95% CI 0.17-0.82). These relationships remained when evaluating live birth/ongoing pregnancy per cycle. In intrauterine insemination cycles, initial strict morphology was associated with subsequent fecundability only when inseminating total motile count was below 5 million. For cycles with total motile count above this threshold, no impact of low morphology on success rates with intrauterine insemination was observed.